Informality among Formal Firms : Firm-level, Cross-country Evidence on tax Compliance and Access to Credit - Gatti, Roberta; Honorati, Maddalena (World Bank, Washington, DC, 2012)
The authors use firm-level, cross-county data from Investment Climate surveys in 49 developing countries to investigate an important channel through which informality can affect productivity: access to credit and external finance. Informality is measured as self-reported lack of tax compliance in a sample of registered firms that also answered questions on a large set of other characteristics. The authors find that more tax compliance is significantly associated with more access to credit both in OLS and in country fixed effects estimates. In particular, the link between credit and formality is stronger in high-formality countries. This suggests that firms' balance sheets are relatively more informative for financial institutions in environments where signal extraction is a less noisy process. The authors' results are robust to the inclusion of a wide array of correlates and to two-stage estimation.